Priming in economics. (December 2016) - Cohn, Alain; Maréchal, Michel André
Highlights: Priming is increasingly used to study the effects of the environment on preferences. We review the literature that uses priming in incentivized economic experiments. A prominent application of priming is the behavioral influence of norms and culture. We also discuss objections to priming and promising avenues for future research. Abstract : Conceptual priming has become an increasingly popular tool in economics. Here, we review the literature that uses priming in incentivized experiments to study economic questions. We mainly focus on the role of social identity, culture, and norms in shaping preferences and behavior. We also discuss recently raised objections to priming research and conclude with promising avenues for future research.